The interpretation and prediction of event participants in Mandarin verb-final active and passive sentences - Gerwien, Johannes (Journal of cultural cognitive science, 2019)
The role of the markers bèi and bǎ for thematic role assignment in Chinese NP1-marker-NP2-V sentences was investigated in adult native speakers. While word order is identical, thematic roles are distributed reversely in these structures [patient-bèi-agent, (passive); agent-bǎ-patient, (active)]. If Mandarin speakers interpret NP1 as the agent of an event, viewing behavior was expected to differ between conditions for NP1-objects, indicating the revision of initial role assignment in the case of bèi. Given reliability differences between markers for role assignment, differences in anticipatory eye movements to NP2-objects were expected. 16 visual stimuli were combined with 16 sets of sentence pairs; one pair partner featuring a bèi-, the other a bǎ-structure. Growth curve analysis of 28 participants’ eye movements revealed no attention differences for NP1-objects. However, anticipatory eye movements to NP2-objects differed. This suggests that a stable event representation is constructed only after NP1 and the marker have been processed, but before NP2. As a control variable, syntactic/semantic complexity of NP1 was manipulated. The differences obtained indicate that the visual world paradigm is in principle sensitive to detect language-induced processing costs, which was taken to validate the null-finding for NP1. Interestingly, NP1 complexity also modulated predictive processing. Findings are discussed with respect to a differentiation between interpretative and predictive aspects incremental processing.